Analisis Resepsi Followers Akun Instagram @radarbogor.id dalam Konsumsi Berita Lokal - Josephine Lahagu; Abung Supama Wijaya (Router : Jurnal Teknik Informatika dan Terapan, 2025)
Social media has become one of the main channels for disseminating information, including local news relevant to people’s daily lives. This study aims to analyze the reception of followers of the Instagram account @radarbogor.id in consuming local news. The research used a qualitative approach with a reception analysis method based on Stuart Hall’s theory, which classifies audience responses into dominant-hegemonic, negotiated, and oppositional positions. Data collection was conducted through in-depth interviews with three informants who actively follow the account. The results show that the followers tend to interpret the content from dominant-hegemonic and negotiated positions. They consider the @radarbogor.id account to be a reliable and up-to-date news source, though some still independently verify the information. Factors that influence positive reception include the informative nature of the content, visually appealing design, and simple language. However, criticism was noted regarding the poor audio quality in video uploads, which can affect audience engagement. This study concludes that social media followers are not passive consumers but active interpreters of media messages who critically evaluate the information they receive.